INTERNATIONAL AND NATIONAL LEGAL GUARANTEES FOR INVESTMENT ACTIVITIES IN UZBEKISTAN - Rakhmonkulova Nilufar Khodzhi-Akbarovna; Shakhlo Bakhadirova Babirovna (Scientific Journal of Pedagogy and Economics, 2021)
The article analyzes international and national guarantee investment activities on the territory of the Republic of Uzbekistan and discusses the issues of the implementation of the rights and legitimate interests of foreign investors using legal guarantee obligations in the national legislation of Uzbekistan. The aim of the study is to study the international mechanism for guaranteeing the repatriation of foreign investors, a comprehensive analysis of the most important international legal mechanisms in this area. The scientific novelty of the research is determined by the fact that the raised problem became for the first time the subject of a special comprehensive study. The author carries out research based on a significant number of international legal acts in the field of international legal guarantees for investment activities, constituent documents of intergovernmental organizations-subjects of international law, conducts a comparative analysis of various aspects of guarantees for investment activities. The novelty of the article is also enhanced by the fact that the author studies in detail the problems of correlation between the international legal and national legal mechanisms for guaranteeing investment activity. In the article, based on the analysis of international legal material, for the first time are investigated: - the international legal mechanism for guaranteeing investment activities, its constituent elements; the operation of multilateral and bilateral agreements in this area; -national legal mechanism for guaranteeing investment activities; To achieve this goal, taking into account the designated subject of research, the following results were obtained in the work:  International legal guarantees have been studied and a legal description to them has been given;  The main aspects of interaction between the international and national legal mechanism for guaranteeing investment activity have been identified;